Göngyöleg nyilvántartás integrálása a gyártásvezető IPBS programba a Leier Hungária Kft. példáján keresztül - Horváth Orsolya (2019)
In my thesis I show the integration of empties management on the example of Leier Hungária Ltd., emphasising the activity of the plant in Jánossomorja, because I spent my vocational practice there. The aim of my paper is to show the multinational venture, whose main activity is construction industry, besides this it utilises property and handles automobile distribution. The venture has an extraordinary wide product range, production process happens locally. The Ltd. produces the finished parts based on customer orders; the transportation tasks are coordinated by the venture’s logistics department. The venture works in a wholesaler system. In order to keep its partner relationships and to increase those, the adequate marketing activity is outstandingly important in the life of the company. In the first part of my thesis I describe Leier Hungária Ltd., its work and activities based on the above listed. During my practice I participated in the work of the logistics department. Knowing its activity, in my thesis I describe the documents applied during the transportation prac-tice as well as the computer register systems which usage helps to attend the logistical, more specifically the empties management tasks. Because of the growing demands towards the logistics department, the customer-oriented point of view and the necessity of up to date databases, it was essential to imple-ment a new computer system. In the last part of my paper this new system is shown, the IPBS, which integration is still in progress, certain parts were introduced in the near past. The usage of the new software is in parallel with the old one, certain modules are in testing phase or under development. This IT system will later replace the charts that are in use now, so the transportation activity processes and the empties management registers of Lei-er Hungária Ltd. will be in command in an integrated structure.